18F-FDG PET/CT Findings of a Recurrent Adenocarcinoma Arising From Malignant Transformation of Abdominal Wall Endometriosis. (February 2015) - Jiang, Maoqing; Chen, Ping; Sun, Long; Huang, Qiuli; Wu, Hua
Abstract : Abstract: Abdominal wall endometriosis (AWE) is defined as endometrial tissue located superficial to the peritoneum, which usually develops in a surgical scar of cesarean delivery. Malignant transformation of AWE is a very rare disease. The most frequent histotype of malignancy developing from AWE is endometrioid adenocarcinoma. We present 18 F-FDG PET/CT findings in a 37-year-old woman with a recurrent adenocarcinoma arising from malignant transformation of AWE, who underwent a repeat PET/CT scan because of a recurrent mass at the upper right side of the surgical incision after a previous cesarean delivery.